From local adaptation to activism and global solidarity: framing a research and innovation agenda towards true health equity - Friedman, Eric A. (Int J Equity Health, 2017)
The proposal for a global health treaty aimed at health equity, the Framework Convention on Global Health, raises the fundamental question of whether we can achieve true health equity, globally and domestically, and if not, how close we can come. Considerable knowledge currently exists about the measures required to, at the least, greatly improve health equity. Why, then, do immense inequities remain? Building on this basic question, we propose four areas that could help drive the health equity research and innovation agenda over the coming years. First, recognizing that local contexts will often affect the success of policies aimed at health equity, local research will be critical to adapt strategies to particular settings. This part of the research agenda would be well-served by directly engaging intended beneficiaries for their insights, including through participatory action research, where the research contributes to action towards greater health equity. Second, even with the need for more local knowledge, why is the copious knowledge on how to reduce inequities not more frequently acted upon? What are the best strategies to close policymakers' knowledge gaps and to generate the political will to apply existing knowledge about improving health equity, developing the policies and devoting the resources required? Linked to this is the need to continue to build our understanding of how to empower the activism that can reshape power dynamics. Today’s unequal power dynamics contribute significantly to disparities in a third area of focus, the social determinants of health, which are the primary drivers of today’s health inequities. Continuing to improve our understanding of the pathways through which they operate can help in developing strategies to change these determinants and disrupt harmful pathways. And fourth, we return to the motivating question of whether we can achieve health equity. For example, can all countries have universal health coverage that comprehensively meets all of people’s health needs? How to foster the national and global solidarity to achieve such equity? The answers to questions such as these can help point the way to measures, often well outside the narrow realm of technical solutions, to realize the right to health, and to achieve and sustain substantive health equality.